Event‐related potentials in response to cheating and cooperation in a social dilemma game. (16th October 2015) - Bell, Raoul; Sasse, Julia; Möller, Malte; Czernochowski, Daniela; Mayr, Susanne; Buchner, Axel
Abstract: A sequential prisoner's dilemma game was combined with psychophysiological measures to examine the cognitive underpinnings of reciprocal exchange. Participants played four rounds of the game with partners who either cooperated or cheated. In a control condition, the partners' faces were shown, but no interaction took place. The partners' behaviors were consistent in the first three rounds of the game, but in the last round some of the partners unexpectedly changed strategies. In the first round of the game, the feedback about a partner's decision elicited a feedback P300, which was more pronounced for cooperation and cheating in comparison to the control condition, but did not vary as a function of feedback valence. In the last round, both the feedback negativity and the feedback P300 were sensitive to expectancy violations. There was no consistent evidence for a negativity bias, that is, enhanced allocation of attention to feedback about another person's cheating in comparison to feedback about another person's cooperation. Instead, participants focused on both positive and negative information, and flexibly adjusted their processing biases to the diagnosticity of the information. This conclusion was corroborated by the ERP correlates of memory retrieval. Successful retrieval of a partner's reputation was associated with an anterior positivity between 400 and 600 ms after face onset. This anterior positivity was more pronounced for both cooperator and cheater faces in comparison to control faces. The results suggest that it is not the negativity of social information, but rather its motivational and behavioral relevance that determines its processing.